On the Uniformity of Distribution of the ElGamal Signature. - Shparlinski, Igor E. (Applicable algebra in engineering, communication and computing.)
We show that, under some natural conditions,the pairs (r,s) produced by the ElGamal signature scheme are uniformly distributed. In particular this implies that values of r and s are not correlated. The result is based on some new estimates of exponential sums.